Sajtó és megélhetés: Pillanatképek a „Krúdy-gép” történetéből - Wirágh, András (Studia Litteraria, 2021)
Gyula Krúdy was one of the most productive authors of the Hungarian fin de siècle and the interwar period. His productiveness always had to align with the modifications of the contemporary press network, although Krúdy’s growing fame soon made it unnecessary for him to broaden the network of connections manually. The different methods of seriality (republications, new literary and journalistic genres) allowed a kind of automatic publishing strategy. The paper presents these strategies as the episodes of the narrative of the ‘Krúdymachine’ which produced approximately 8-9000 texts during 40 years.